The Cost of Waiting on an Orthopaedic Waiting List: a scoping review - Joanne Morris; Asterie Twizeyemariya; Karen Grimmer (ACHSM, 2017)
Background: Approximately 30% Australians suffer from arthritis and other musculoskeletal disorders. From 2003-2033 there is a predicted 223% increase in expenditure on health management of musculoskeletal disorders. There is evidence of increasing prevalence of orthopaedic complaints, in longer waiting lists for specialist consultations in public hospital outpatient clinics. Little is known about the costs and ramifications of waiting for orthopaedic consultations. Aim: Establish what is known about the direct and indirect costs of being placed on a waiting list for an orthopaedic consultation. Method: Patient and Outcome search strategy of Medline, Embase, Pubmed, NHS Economic evaluation database (NHS-EED) from each database inception date. Handsearching of reference lists of included papers also occurred. A realist synthesis framework underpinned the review, using a ubiquitous patient journey to map available literature on the impact of waiting. Hierarchy of evidence was reported using NHMRC criteria and articles critically appraised using either the PEDRo or CASP criteria (relevant to the design). A purpose-built data extraction instrument was developed. Results: We identified 786 studies, of which 139 were relevant, including a systematic review (Hoogeboom et al) with 15 included articles which were added to the list of eligible papers (and the review itself deleted), leaving 153 included articles; 17 were relevant to the review. Fourteen papers reported on quality of life and four reported on costs, two of these papers reported on both and all were of low to moderate quality. The research was not based on a comprehensive understanding of the stages of waiting, and there were inconclusive outcomes for quality of life and cost. Conclusion: There is scant evidence of the impact on quality of life and costs of waiting for orthopaedic outpatient appointments. Future research should aim for improved methodological quality and use patientfocused quality of life measures, and validated measures of cost. Abbreviations: NHMRC - National Health and Medical Research Council; PROMS - Patient Related Outcome Measures; QoL - Quality of Life; WOMAC - Western Ontario and McMaster Universities Osteoarthritis Index; YLD - Years Lived With Disability